The Impact of Integrated Marketing Communication (IMC) Tools on Learning in B-Schools : A Study - Nema, Geeta; Kasliwal, Kavita (Prabandhan: Indian Journal of Management, 2018)
Management education in India is facing huge domestic and international competition. Question arises of differentiation of B - schools from their competitors. The experience of students with staff of the B-school decides their perception and level of satisfaction while learning in a B-school. The major purpose of this study was to explore whether B-schools were using integrated marketing communications (IMC) tools for learning, and if so, what were the perceptions of students regarding how relevant and appreciable the learning tools were for them. Thus, the objective of this paper was to study the adoption of IMC tools for learning in B-schools of Indore ; 121 respondents of various undergraduate and post graduate courses of government and private B-schools were interviewed with a structured questionnaire. Data analysis, after applying frequency distribution, chi-square, and ANOVA showed that age, course, and income did affect learning in B - schools. The category of B-schools, that is, government or private also affected the learning outcomes. The effect of IMC tools on the learning of students was effective when they were in direct contact in the classroom with the teacher ; whereas, other learning tools, when there was indirect contact between the student and teacher, did not have a positive effect on learning. Accordingly, B-schools must focus on using their resources effectively for only the identified learning tools as mentioned in this paper and thereby, improve the experiences of the students studying in B-schools. This will help in avoiding wastage of resources of B-schools.